ANALISIS HUKUM TENTANG PROSES HIWALAH DALAM HUKUM ISLAM - Rozalita; Sri Bintang; Ivan Domos Saputra; Muhammad Aji Purwanto (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to conduct a legal analysis of the hiwalah process in the context of Islamic law. Hiwalah is an important concept in the Islamic legal system that refers to the transfer of debt liabilities from one party to another. In the perspective of fiqh, hiwalah is considered a valid contract if it meets certain conditions such as the willingness of all parties involved, the existence of clear debts, and compliance with sharia principles. Hiwalah provides convenience for parties involved in financial matters, especially in settling debt and receivables obligations. In contemporary practice, the concept of hiwalah is also used in the Islamic banking and modern finance sectors, particularly in products such as credit transfer and debt management. This research examines the sharia policies on hiwalah, its terms, and its application in the modern context, as well as its potential benefits in creating a fair and ethical financial system.